ChemInform Abstract: Tandem Aza‐Michael/Spiro‐Ring Closure Sequence: Access to a Versatile Scaffold and Total Synthesis of (.+‐.)‐Coerulescine. Issue 32 (18th July 2013) - Goermen, Meral; Le Goff, Ronan; Lawson, Ata Martin; Daich, Adam; Comesse, Sebastien
Abstract A simple protocol is presented for the tandem reaction between Michael acceptors (I) and carbamate (II) to yield pyrrolidine derivatives.